Engineering bacterial vortex lattice via direct laser lithography - Daiki Nishiguchi (Nature Portfolio, 2018)
Geometrically confined suspensions of swimming bacteria can self-organize into an ordered state. Here, the authors use tiny pillars to trigger organization of bacterial motion into a stable lattice of vortices with a long-range antiferromagnetic order and control vortex direction through pillar chirality.